Case report: Innovative approach to esophageal cancer with right aortic arch: neoadjuvant immunotherapy and 3D reconstruction - Luo, Chengwen; Luo, Zhilin (Frontiers in Oncology, 2025)
BackgroundWe report a rare case of locally advanced esophageal cancer with a right aortic arch (RAA), successfully treated with neoadjuvant immunotherapy and minimally invasive esophagectomy, guided by three-dimensional (3D) reconstruction.Case presentationA 50-year-old male with stage III esophageal squamous cell carcinoma (cT3N0M0) and RAA underwent four cycles of neoadjuvant immunotherapy with sintilimab, resulting in significant tumor regression. Minimally invasive esophagectomy was performed with the aid of preoperative 3D reconstruction, which was critical in navigating the complex vascular anatomy and ensuring surgical precision.ConclusionThis case demonstrates the efficacy of neoadjuvant immunotherapy combined with 3D reconstruction in managing esophageal cancer complicated by vascular anomalies. This approach offers a promising alternative for complex cases where conventional treatments pose higher risks.